2006
DOI: 10.1186/1476-0711-5-26
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Sporadic cases of CA-MRSA in persons without risk-factors for MRSA carriage are increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
125
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 315 publications
(136 citation statements)
references
References 20 publications
7
125
1
3
Order By: Relevance
“…Our fi nding that living or working on a farm with animals is associated with CC398 acquisition reinforces results of studies in France, the Netherlands, and Canada that indicated that CC398 is transmissible from animals to humans (3,4,6,7). Also in the Netherlands, a CC398 prevalence of 3.9% in 179 veterinarians has been de-scribed; all positive persons had recent or regular contact with pigs and cows (22).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Our fi nding that living or working on a farm with animals is associated with CC398 acquisition reinforces results of studies in France, the Netherlands, and Canada that indicated that CC398 is transmissible from animals to humans (3,4,6,7). Also in the Netherlands, a CC398 prevalence of 3.9% in 179 veterinarians has been de-scribed; all positive persons had recent or regular contact with pigs and cows (22).…”
Section: Discussionsupporting
confidence: 72%
“…We provide evidence for pigs being a substantial reservoir of human MRSA CC398 in Denmark, as appears to be the case in other European countries such as the Netherlands and France (3,4,7,12), and in Canada (6).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations